2021
DOI: 10.1186/s41256-021-00227-x
|View full text |Cite
|
Sign up to set email alerts
|

Addressing constraints to informal providers’ involvement in tuberculosis control: a qualitative study of patent medicine dealers and tuberculosis programme managers

Abstract: Background A major constraint to tuberculosis control is low case finding with under-reporting to national authorities. Evidence shows that Patent Medicine Dealers are first port of call for most people with symptoms of tuberculosis, yet there is poor referral of such clients to tuberculosis treatment facilities for further evaluation. This study investigated constraints to involvement of Patent Medicine Dealers in tuberculosis control. Methods Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Our results indicate that poor socioeconomic characteristics and low TB-related health literacy together impede TTMS delivery. As patients with low socioeconomic features were often found to have a lower educational background, poor health literacy, and were more likely to be non-adherent, they were more likely to refuse HCWs’ supervision, which is consistent with other studies 18 53 54. In addition, we found that TTMS delivery among migrant patients was challenging for HCWs because it was difficult to reach them.…”
Section: Discussionsupporting
confidence: 90%
“…Our results indicate that poor socioeconomic characteristics and low TB-related health literacy together impede TTMS delivery. As patients with low socioeconomic features were often found to have a lower educational background, poor health literacy, and were more likely to be non-adherent, they were more likely to refuse HCWs’ supervision, which is consistent with other studies 18 53 54. In addition, we found that TTMS delivery among migrant patients was challenging for HCWs because it was difficult to reach them.…”
Section: Discussionsupporting
confidence: 90%
“…The low patronage of other places/informal sector of care reported in current study is good as they contribute to delay in accessing quality care, prolonged transmission of diseases and consequently hampers TB control. For instance, a study in Ebonyi State, Nigeria reported that practices toward presumptive TB clients among PPMVs were poor as shown in their inadequate referral of clients with persistent cough to DOTS facilities, prolonged treatment of clients with persistent cough with antibiotics which have anti TB activity and untimely poor referral of clients for diagnosis and treatment [30]. The PMVs lack knowledge about tuberculosis signs, symptoms and have possessive mode of operation of care service [31].…”
Section: Discussionmentioning
confidence: 99%
“…29 This necessitates that systematic screening for comorbidities, prompt diagnosis, and management of other infections be carried out in clinically diagnosed cases. 30,31 Second to the highest proportion of TB cases among the screened populations is PLWH. It is established that PLWH are 20 times more likely than those without HIV to become sick with TB because HIV weakens the immune system, which makes it harder for the body to fight TB bacilli.…”
Section: Box Variables Assessed In An Activementioning
confidence: 99%